Expression of connexin 43 protein in cardiomyocytes of heart failure mouse model - Liu, Shaoyan; Lan, Yang; Zhao, Yun; Zhang, Qianyu; Lin, Tzuchun; Lin, Kaibin; Guo, Junjie; Yan, Yan (Frontiers in Cardiovascular Medicine, 2022)
Heart failure (HF) is the end stage of various cardiovascular diseases, with high morbidity and mortality, and is associated with a poor prognosis. One of the primary causes of HF is aortic valve disease, manifested by progressive aortic valve stenosis (AVS), resulting in increased left ventricular load, ventricular hypertrophy, ultimately ventricular dysfunction, and HF. Early assessment of the degree of cardiomyopathy and timely intervention is expected to improve patients’ cardiac function and delay or even avoid the occurrence of HF. The Wnt signaling pathway is mainly involved in regulating myocardial insufficiency after valve stenosis. Connexin 43 protein (Cx43) is an essential target of Wnt signaling pathway that forms gap junction (GJ) structures and is widely distributed in various organs and tissues, especially in the heart. The distribution and transformation of Cx43 among cardiac cells are crucial for the development of HF. To specifically label Cx43 in vivo, we established a new Cx43-BFP-GFP mouse model with two loxp sites on both sides of the tag BFP-polyA box, which can be removed by Cre recombination. This double-reporter line endowed us with a powerful genetic tool for determining the area, spatial distribution, and functional status of Cx43. It also indicated changes in electrical conduction between cells in a steady or diseased state.